Aplikasi Media Sosial sebagai Alat Politik Donald Trump (Netnografi Cuitan Trump di Twitter) - Yohanes Ivan Adi Kristianto; Hanna Nurhaqiqi (Universitas Mataram, 2021)
Every political actors, either at local, national, or global levels, tends to demonstrate their characteristics, including Donald John Trump. Different from his predecessors, Trump decides his communication style by using simple, easily understood, and solid words. Meanwhile, for the media, Trump tends to prioritize social media, such as Twitter, as his tool. Using the concept of CNN Effect and Agenda-Setting, this paper aims to analyze the interests of Trump in using Twitter as the communication tools and verify the concept of CNN Effect by using the case study of the Trump’s utilization of social media. Then, by applying agenda setting, the authors analyze the content of Trump’s tweet and the interests following. Literature study is fully applied in this paper. Whereas, the time scope of this research is limited from Trump’s campaign period until September 2020. This research argues that the effects of Trump’s tweets in his Twitter account have similar implications with the concept of CNN Effect. This also confirms that CNN Effect can occur not only in mass media, but also in social media. Secondly, the paper argues that Trump consistently voice particular issues through his Twitter account in order to achieve his plans manifested in his campaign.